Structural health monitoring of an operational bridge: A case study. (15th September 2019) - Gatti, Marco
Highlights: SHM codes, guidelines and recommendations. SHM dynamic load test in Italian regulation. Dynamic load test and static load test compared. Abstract: During testing of the structural reliability of a prestressed reinforced concrete bridge built in the late 1960s, the author compared the structural responses, performances and costs of jointly conducted static and dynamic load tests. In the static load test, the precision spirit leveling technique was used to measure the deflections of the deck induced by four trucks weighing about 36 tonnes each. In the dynamic load test, accelerometers placed on the main beam were used to measure the vibration frequencies following an impulse produced by a 2-tonne truck. The dynamic load test resulted in a refined finite element model of the bridge. The comparison showed that the dynamic load test can supplement the static load test for the structural testing of new bridges or be an alternative to it for the monitoring of operational bridges.